Mineralogy, petrology, geochemistry, and chronology of the Murrili (H5) meteorite fall: The third recovered fall from the Desert Fireball Network. (12th February 2021) - Anderson, S.; Benedix, G. K.; Forman, L. V.; Daly, L.; Greenwood, R. C.; Franchi, I. A.; Friedrich, J. M.; Macke, R.; Wiggins, S.; Britt, D.; Cadogan, J. M.; Meier, M. M. M.; et al.
Abstract: Murrili, the third meteorite recovered by the Desert Fireball Network, is analyzed using mineralogy, oxygen isotopes, bulk chemistry, physical properties, noble gases, and cosmogenic radionuclides. The modal mineralogy, bulk chemistry, magnetic susceptibility, physical properties, and oxygen isotopes of Murrili point to it being an H5 ordinary chondrite. It is heterogeneously shocked (S2–S5), depending on the method used to determine it, although Murrili is not obviously brecciated in texture. Cosmogenic radionuclides yield a cosmic ray exposure age of 6–8 Ma, and a pre‐atmospheric meteoroid size of 15–20 cm in radius. Murrili's fall and subsequent month‐long embedment into the salt lake Kati Thanda significantly altered the whole rock, evident in its Mössbauer spectra, and visual inspection of cut sections. Murrili may have experienced minor, but subsequent, impacts after its formation 4475.3 ± 2.3 Ma, which left it heterogeneously shocked.